KESADARAN MASYARAKAT DALAM MELAKSANAKAN PERKAWINAN KE DUA SETELAH PERCERAIAN BERDASARKAN PUTUSAN PENGADILAN DI PASAMAN BARAT - Rita Faura; Rangga Prayitno (Ekasakti Jurnal Penelitian dan Pengabdian, 2022)
Abstract: Polyandry marriages have taken place in Ranah Batahan, West Pasaman. There are 2 (two) polyandry marriages. From the two examples of polyandry marriages that the author described above, actually a valid marriage is when the husband and wife are divorced, and the wife may marry another man. However, in the case of a polyandry marriage that occurred in Ranah Batahan, West Pasaman, it was not carried out according to the proper procedure, namely through the first divorce. Proof of divorce can only be proven by a divorce certificate based on Article 8 of the Compilation of Islamic Law which states that marriage decisions other than divorce can only be proven by divorce certificates in the form of decisions of the Religious Court in the form of divorce decisions, divorce pledges, chuuk or decisions to take talak. In fact, the biggest difficulty in polyandry that causes the failure of this marriage in practice is the unknown father of the child being born, so that in this marriage model the relationship between father and child becomes uncertain. From the results of the research, the community's weak legal awareness in carrying out the second dispute after a court decision was caused by a lack of education and knowledge of the community, coupled with the customary customs of the community and the existence of economic factors, especially for polyandry couples that occurred in the Batahan West Pasaman Realm while efforts to make the community aware of having Legal decisions that remain divorced before the second marriage are carried out by understanding the existence of positive marriage law and Islamic law and providing legal sanctions against the cancellation of polyandry marriages so that this method reduces the practice of polyandry marriages in Ranah Batahan, West Pasaman. Abstrak: Pernikahan poliandri telah terjadi di Ranah Batahan, Pasaman Barat. Ada 2 (dua) pernikahan poliandri. Dari kedua contoh perkawinan poliandri yang penulis uraikan di atas, sebenarnya perkawinan yang sah adalah apabila suami istri bercerai, dan istri boleh menikah dengan laki-laki lain. Namun dalam kasus perkawinan poliandri yang terjadi di Ranah Batahan, Pasaman Barat, tidak dilakukan sesuai prosedur yang semestinya, yakni melalui perceraian pertama. Pembuktian cerai hanya dapat dibuktikan dengan akta cerai berdasarkan Pasal 8 Kompilasi Hukum Islam yang menyatakan bahwa putusan perkawinan selain cerai hanya dapat dibuktikan dengan akta cerai berupa putusan Pengadilan Agama di berupa putusan cerai, ikrar cerai, chuuk atau putusan ambil talak. Padahal, kesulitan terbesar dalam poliandri yang menyebabkan gagalnya perkawinan ini dalam praktiknya adalah tidak diketahuinya ayah dari anak yang dilahirkan, sehingga dalam perkawinan model ini hubungan ayah dan anak menjadi tidak pasti. Dari hasil penelitian, lemahnya kesadaran hukum masyarakat dalam melaksanakan perkawinan kedua setelah adanya putusan pengadilan disebabkan kurangnya pendidikan dan pengetahuan masyarakat, ditambah lagi dengan kebiasaan adat masyarakat serta adanya faktor ekonomi khususnya bagi pasangan poliandri yang terjadi di Ranah Batahan Pasaman Barat sedangkan upaya menyadarkan masyarakat agar memiliki keputusan hukum yang tetap cerai sebelum perkawinan ke 2 dilakukan dengan memahami adanya hukum perkawinan positif dan Islam hukum dan memberikan sanksi hukum terhadap pembatalan perkawinan poliandri sehingga cara ini mengurangi praktek perkawinan poliandri di Ranah Batahan, Pasaman Barat.